The Problematics Online Lectures on Human Resource Management Courses (HRM) at The Islamic College Level - Sedya Santosa; Aulia Diana Devi (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This study aims to find out how the problem of online learning experienced by students in human resource management (HRM). This type of research is descriptive qualitative research where the samples used are 10 students of MPI State Islamic University Sunan Kalijaga Yogyakarta. Data collection techniques use primary data sources obtained through interviews and secondary data sources obtained through online media. Data analysis is by data collection, data reduction, data display, and conclusion drawing. The results showed that in the implementation of online learning, human resource management lectures (HRM) are conducted using mobile phones or laptops through zoom meeting applications and WhatsApp groups. Problems experienced during the lecture process are constrained related to the unstable network and lack of enthusiasm of students in discussions during lecture activities. This is the basis of problematika that makes online learning less conducive and effective. To overcome these problems, educators or lecturers can create interesting and innovative learning innovations, so that learning can run well in accordance with the goals to be achieved.